The The Impact of Problem-Based Workshops on Improving Teacher Competency in Designing Learning Based on Environmental Potential - Fatni Mufit (Pelita Eksakta, 2020)
The competence of science teachers in Padang City Junior High Schools in developing learning tools is still low, as revealed by the teacher's pre-test abilities before the workshop is held. Pre-test includes gathering information about learning resources, learning media, models / methods / approaches, and assessment instruments used by teachers not yet utilizing the environment. Referring to the problems of teachers, problem-based workshop activities are designed in an effort to improve teacher competencies in designing learning tools based on environmental potential. Problem-based workshops have stages: (1) problem identification, (2) Focusing on problems, (3) Finding alternative solutions, (4) Presentation of solutions; (5) Implementation and (6) Reflection & follow-up. The workshop was attended by 20 junior high school science teachers in Padang city. The workshop activities consisted of 2 parts, namely the workshop activities at FMIPA UNP and the Implementation activities at SMP 25 Padang. Problem-based workshops succeeded in increasing teacher competence in designing IPA-based environmental learning tools. The results of the implementation of the workshop products by the teacher showed a positive influence on student involvement and activity in learning